Trends in the use of protozoa in the assessment of wastewater treatment - Nicolau, Ana (2001)
Increasing environmental pollution and the continuous development of new chemicals and drugs has led to ever growing concern about the potential effects of these compounds directly or indirectly on human health. As concerns water pollution, protozoa seem to be an excellent tool to assess both toxicity and pollution: they are regarded as biological indicators of pollution when their presence or absence can be related to particular environmental conditions, and they are considered test organisms when a species or population is used to evaluate the toxicity of relevant toxic compounds. Thus, an integrated approach is being developed to assess how toxic compounds affect the different biological levels of organisation – from the community level to the species level – of ciliated protozoa. The present paper reports and discusses the current state of the art of this approach.